Comparison Between Correlation of Creative Thinking Skills and Learning Results, and Correlation of Creative Thinking Skills and Retention in the Implementation of Predict Observe Explain (POE) Learning Model in Senior High Schools in Malang, Indonesia - Frengky Neolaka; Aloysius Duran Corebima (ÜNİVERSİTEPARK Limited, 2018)
This correlational research was conducted in order to uncover the correlation between creative thinking skills and learning results, as well as between creative thinking skills and retention in the implementation of Predict Observe Explain (POE) learning model. The population of this research were students of Class X senior high schools in Malang, Indonesia, in the odd semester of 2017/2018 academic year. The sample used was F1 class students of Senior High School 5 Malang. The results of simple linear regression analysis show that creative thinking skills correlate with learning results through the implementation of POE learning model. The contribution of creative thinking skills toward learning results was as much as 32%. However, creative thinking skills do not correlate with students' cognitive retention. Students may experience difficulties retrieving information stored in their memory because new knowledge is stored only in their short-term memory. Factors that might have caused this to occur are that students only learn in order to pass examinations. Learning is undertaken in order to obtain high exam scores and when students are forced to complete assignments, but they do not continue learning afterwards